Photoelectrochemical Performance of MoBiInSe5 Mixed Metal Chalcogenide Thin Films. (2015) - Mane, R.M.; Mali, S.S.; Ghanwat, V.B.; Kondalkar, V.V.; Khot, K.V.; Mane, S.R.; Shinde, D.B.; Patil, P.S.; Bhosale, P.N.
Abstract: We have successfully constructed MoBiInSe5 thin film through facile Arrested Precipitation Technique (APT). FurtherOptostructural, morphological and photoelectrochemical properties were investigated. The precursors used were molybdenum, bismuth, Indium triethanolamine complexes (TEA) along with organic additives.Ammonium molybdate, Bismuth nitrate, Indium sulphate and sodium selenosulphite were used as sources of Mo 4+, Bi 3+, In 3+ and Se 2 .The optical band gap energy of thin film was estimated to be 1.47 eV. X-ray diffraction (XRD) data reveals that grown MoBiInSe5 thin film was highly nanocrystalline with orthorhombic crystal structure.Atomic Force Microscopy (AFM)&Scanning electron microscopy (SEM) studies reveal that porous layer having elongated fibrous morphology with high surface area. The film was obtained with a well-defined composition, very close to the expected atomic percentage. PEC application of prepared thin film were checked in Sulphide/Poly sulphide redox electrolyte which revealed that photoactive MoBiInSe5 thin film deposited on FTO coated glass exhibited maximum values of fill factor (FF) and conversion efficiency (η) with n type semiconductor nature.